Advice for Working Dads - Review, Harvard (Ascent Audio, 2021)
Gone are the days when fathers were expected to put work first and family last. Today, men worldwide are redefining fatherhood and finding greater fulfillment both at work and at home. But old ways die hard. Many managers prefer the status quo, and fathers aren't finding the support and flexibility they need from their employers. Dads still feel pressure to downplay or hide their involvement in their children's lives. And even as more men step up as parents, across every level of society the burdens of parenting and running a household still fall unfairly on women. Fatherhood is one of the toughest jobs and the biggest responsibility you'll ever take on. Advice for Working Dads will teach you how to balance and integrate work and parenthood, how to navigate the common pitfalls at work, and how to find success when you're taking on twice as much-for the good of your family. This volume will help you: navigate workplaces and bosses that want you to forget you're a parent; spend your time at work and at home more purposefully; make time for yourself, your friends, and your hobbies; set reasonable expectations and limits in the always-on work culture; communicate better with your spouse or partner about careers, parenting, and housework; get the paternal leave you and your family need; set your family up for success; and more.